Scheimpflug Imaging Parameters Associated with Tear Mediators and Bronchial Asthma in Keratoconus - Dorottya Pásztor; Bence Lajos Kolozsvári; Adrienne Csutak; András Berta; Ziad Hassan; Beáta Andrea Kettesy; Péter Gogolák; Mariann Fodor (Journal of Ophthalmology)
Purpose. To determine associations between mediators in tears in the whole spectrum of keratoconus (KC); to explore connections between mediators and Scheimpflug parameters; to examine correlations between Scheimpflug parameters and bronchial asthma. Methods. Tear samples were collected from 69 patients and 19 controls. Concentrations of mediators—IL-6, -10; CXCL8, CCL5; MMP-9, -13; TIMP-1; t-PA, PAI-1—were measured by Cytometric Bead Array. Measured Pentacam parameters include keratometry values (K1, K2, Kmax), corneal thickness (Pachy Pupil, Apex, Min), and elevations and indices (including Belin-Ambrósio deviation (BAD-D)). Results. A number of significant positive associations were observed between pairs of mediator concentrations. Significant positive correlations were found between BAD-D and CXCL8/MMP-9 and K2 and MMP-9. Significant negative associations were explored between Pachy Min and CXCL8/t-PA. Significant associations were found between pairs of mediators (IL-6 and CXCL8; CCL5 and CXCL8/MMP-9; TIMP-1 and MMP-9/-13/t-PA; t-PA and CXCL8/CCL5/PAI-1) and the severity of KC. Significant positive correlation between asthma and the severity of KC was explored. Conclusion. Cooperation of different mediators in tears all taking part in the complex pathomechanism of keratoconus was revealed. Our research verifies that inflammation plays a crucial role in the pathogenesis of KC. Additionally this study confirms the effect of bronchial asthma on keratoconus.